1996
DOI: 10.1039/jm9960601889
|View full text |Cite
|
Sign up to set email alerts
|

Structural relaxation and crystallization of semiconducting vanadate glass accompanying a jump of the electrical conductivity

Abstract: The 57Fe Mossbauer spectrum of semiconducting xK,O (90-x)V205 * 10Fe203 glasses (20 < x d 30) consists of a quadrupole doublet peak. The linewidth and the quadrupole splitting decreased gradually after heat treatment at the crystallization temperature, reflecting an increased uniformity of Fe-0 bonds and a decreased distortion of FeO, tetrahedra, respectively. FTIR spectra of heat-treated vanadate glasses revealed an evident peak separation between VO, and FeO, tetrahedra. The FeO, units were not observed in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Prolonged isothermal annealing of 25 K2O • 10 Fe2O3 • 65 V2O5 glass for more than 150 min resulted in a gradual decrease of σ in conjunction with the precipitation of "insulating" KV3O8 particles. [4,5] A Kissinger plot of Tc in the differential thermal analysis (DTA) of x K2O • 10 Fe2O3 • (90 -x) V2O5 glasses (x = 20 -35) showed that the crystallization was triggered by the cleavage of Fe III -O bonds forming distorted FeO4 tetrahedra with the Fe III -O bond energy of 2.6 eV. These experimental results suggested that the crystallization of glass (precipitation of crystalline particles or phase in the glassy phase) was not related to the increase in σ, but to the structural relaxation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolonged isothermal annealing of 25 K2O • 10 Fe2O3 • 65 V2O5 glass for more than 150 min resulted in a gradual decrease of σ in conjunction with the precipitation of "insulating" KV3O8 particles. [4,5] A Kissinger plot of Tc in the differential thermal analysis (DTA) of x K2O • 10 Fe2O3 • (90 -x) V2O5 glasses (x = 20 -35) showed that the crystallization was triggered by the cleavage of Fe III -O bonds forming distorted FeO4 tetrahedra with the Fe III -O bond energy of 2.6 eV. These experimental results suggested that the crystallization of glass (precipitation of crystalline particles or phase in the glassy phase) was not related to the increase in σ, but to the structural relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Isothermal annealing at 380 °C caused a substantial decrease in ρ from 1.6 × 10 7 Ω cm (σ = 6.3 × 10 -8 S cm -1 ) to 2.3 × 10 3 Ω cm (σ = 4.3 × 10 -4 S cm -1 ). [4,5] Nishida et al suggested that the lowering of ρ by four orders of magnitude was due to an increased probability of the small polaron hopping from V IV (or V III ) to V V . The decrease in quadrupole splitting (Δ) of Mössbauer spectra measured at room temperature (RT) confirmed a decrease in the distortion of pseudo-1D network structure of 25 K2O • 10 Fe2O3 • 65 V2O5 glass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) Vanadate glasses are known to have semiconductivity caused by electron hopping from V IV to V V . 6) Vanadium pentoxide (V2O5) is known to have a layered structure composed of VO5 pyramids. 6 The different slope of the straight line suggests that the chemical bond of NWF-oxygen polyhedra is much more intense than that of NWM-oxygen polyhedra and also the chemical bond of NWF-oxygen tetrahedra is more intense than that of NWF-oxygen octahedra since the former is more covalent than the latter.…”
Section: Introductionmentioning
confidence: 99%
“…6) Vanadium pentoxide (V2O5) is known to have a layered structure composed of VO5 pyramids. 6 The different slope of the straight line suggests that the chemical bond of NWF-oxygen polyhedra is much more intense than that of NWM-oxygen polyhedra and also the chemical bond of NWF-oxygen tetrahedra is more intense than that of NWF-oxygen octahedra since the former is more covalent than the latter. In this paper, Mössbauer spectra of xLi2O·2FeO·V2O5·P2O5 and xNa2O·2FeO·V2O5·P2O5 glasses (x = 0, 0.5, 1.0 and 1.5), developed for a cathode material of Li-ion battery, were measured for determining the local structure Fe III .…”
Section: Introductionmentioning
confidence: 99%